Experimental investigation on the effect of Leading Edge Tubercles on the Performance of Marine Propellers in fully wet condition. (1st July 2022) - Falchi, Massimo; Ortolani, Fabrizio; Shi, Weichao; Stark, Callum; Aloisio, Giovanni; Grizzi, Silvano; Dubbioso, Giulio
Abstract: Leading edge tubercles ( L E T ) is an attractive passive flow control solution that has been proved to enhance the hydrodynamic performance and efficiency of lifting surfaces adopted in many engineering areas. Nonetheless, their industrial application in control and propulsion devices of marine vehicles is still at the beginning. To move further steps ahead, a preliminary experimental campaign for a five bladed Wageningen B-screw propeller modified with three different configurations of leading edge tubercles was carried out in cavitation free conditions. In particular, the propellers were tested in open water conditions in straight and oblique flow at incidences of 10 ° and 20 °, with the aim to study the effects of L E T during steady and moderate unsteady conditions. The propellers are tested at two different chord Reynolds numbers in order to investigate their applicability also to small autonomous marine vehicles. The analysis proved that suitable layout of tubercles can enhance the hydrodynamic efficiency in axial symmetric flow while reducing undesired effects caused by operation in off-design. Highlights: Open water tests on different configurations of propellers with leading edge tubercles. Evaluation of tubercles' wavelength and amplitude effects. Propeller in axial and oblique flow (off-design).